Evaluation of the combination effect of rutin and vitamin C supplementation on the oxidative stress and inflammation in hemodialysis patients - Omar, Samia; El Borolossy, Radwa Maher; Elsaid, Tamer; Sabri, Nagwa A. (Frontiers in Pharmacology, 2022)
Hemodialysis (HD) patients are at risk of malnutrition and cardiovascular complications and all-cause mortality due to oxidative stress and inflammation. Some studies demonstrated that Rutin attenuates oxidative stress and inflammation, in CKD rats, but its effects in HD patients are unknown up to date. The aim of this study was to evaluate the effect of combination of Rutin and Vitamin C versus Vitamin C alone on the oxidative stress and inflammation in HD patients. A prospective randomized, open-label, controlled trial was enrolled on hundred and five HD patients divided into three groups as follows; patients in group 1 were given Rutin /Vitamin C combination (Ruta C group as the combination Trade name is known as Ruta C 60 Tablets), group 2 were given Vitamin C (1g) (Vitamin C group) and group 3 was the control group, the study period was 16 weeks. The following were assessed at baseline and at the end of the study; serum malondialdehyde (MDA), glutathione peroxidase (GPx), high sensitivity C-reactive protein , tumor necrosis factor-α, lipid profile levels and erythrocyte sedimentation rate. It was found that Vitamin C significantly increased serum GPx in group2 (P=0.001) compared to a non-significant results in both group 1 and 3, besides, serum MDA and TNF-α values had decreased significantly in the 3 groups compared to their baselines, however a non-significant difference was seen among the studied groups at end of study. On the other hand, MDA levels were reduced by 50% in the interventional groups compared to 28% in the control group, while, Ruta C group showed 80% reduction in the level of TNF α compared to 78% reduction observed in the vitamin C group and finally the interventional drugs showed a significant improvement in the lipid profile. Vitamin C supplementation alone for 16 weeks had a potential effect on the antioxidant’s GPx activity. Moreover, it was reported that both Vitamin C alone and Rutin/Vitamin C combination showed a protective role against lipid peroxidation evidenced by the reduced levels of MDA. Finally, Rutin had a favourable synergistic effect with Vitamin C in reducing TG, TNF-α levels, and increasing HDL-C level.